Research on Transformation Efficiency of Scientific and Technological Achievements in Henan Province of China Based on Three-Stage DEA Model - Pan Yang; Panpan Liu (Decision Making: Applications in Management and Engineering, 2025)
The transformation of scientific and technological achievements (TSTA) constitutes a central mechanism for advancing an innovation-led development agenda and plays a vital role in strengthening innovation capacity within Henan Province. To support the long-term improvement of the transformation efficiency of scientific and technological achievements in Henan and comparable urban areas (TESTA), this study applies a combined three-stage Data Envelopment Analysis (DEA) and Malmquist Index (MI) approach to assess both the static and dynamic characteristics of TESTA across 18 cities in the province. In addition, the Dagum Gini coefficient is utilised to measure disparities in TESTA across regions and to decompose their respective contributions. The main outcomes indicate the following: (1) TESTA levels in Henan are strongly shaped by governmental investment in science and technology, the prevailing research climate, and overall economic conditions within each locality. (2) Once external environmental influences and stochastic disturbances are filtered out, the TESTA of most cities shows a marked reduction relative to baseline results, accompanied by substantial variability across regions. (3) Analysis of the MI and its decomposed indices demonstrates that shifts in technological progress (Tech) serve as the principal endogenous force underpinning TESTA. (4) Findings from the Dagum Gini coefficient reveal that variations between regions are the major source of inequality in the provincial development of TSTA. Collectively, these insights offer practical guidance for decision-makers seeking to strengthen TESTA, highlighting the importance of enhancing scale efficiency, accelerating technological advancement, and adopting region-specific development pathways.